Les Archives de France en 1978 (Archives et bibliothèques de Belgique (ABB), 1979)

Loi n° 79-18 du 3 janvier 1979 sur les archives (Gazette des archives, 1979)

Une lecture méconnue de l'histoire : le service des cartes et plans aux Archives nationales (Culture et Communication, 1979)

La Commission de coordination de la documentation administrative et les Archives de France - Blaquière, Henri (Gazette des archives, 1979)

Les Archives de France et les archives d'entreprises - Brot, Isabelle (Gazette des archives, 1979)

La loi du 3 janvier 1979 (France) et la communication des documents - Charpy, Jacques (La Gazette des archives, 1979)

Les archives du groupe Rhône-Poulenc - Chomereau, Aymar de (La Gazette des archives, 1979)

Les innovations apportées par la loi du 3 janvier 1979 (France) - Duchein, Michel (La Gazette des archives, 1979)

Comment fut élaborée et votée la loi sur les archives du 3 janvier 1979 - Ducrot, Ariane (Gazette des archives, 1979)
How the Archives Law of 3 January, 1979, was prepared and voted. What were the aims of the French Archives when the new Archives Law was initiated. Analysis of the debates in Parliament about the Law : how they illustrate the basic problems of archives (especially the contradiction between (1) the right of information and the right of privacy, (2) the right of private property, the needs of researchers and the conservation of the historical heritage) ; to what extent the original project was modified by Parliament ; what is to be expected from the new Law.

La loi du 17 juillet 1978 (France) : de la liberté d'accès aux documents administratifs - Gorgeon-Demartres, A. (La Gazette des archives, 1979)

La loi du 3 janvier 1979 (France) et le traitement des documents postérieurs à 1940 - Gut, Christian (La Gazette des archives, 1979)

Saint-Gobain-Pont-à-Mousson et les archives - Hamon, Maurice (Gazette des archives, 1979)

Saint-Gobin-Pont-à-Mousson et les archives - Hamon, Maurice (La Gazette des archives, 1979)

Problèmes de conservation à la Bibliothèque nationale de Paris - Labarre, Albert (Archives et bibliothèques de Belgique (ABB), 1979)

Quel avenir pour les archives du ministère de la Défense ? - Le Maresquier, Erik (Gazette des archives, 1979)

Les archives nationales (France) en 1978 - Menier, Marie-Antoinette (La Gazette des archives, 1979)

L'association des archivistes français - Taillemite, Étienne (Gazette des archives, 1979)
Founded in 1904, this Association, which is now 75-year old, has a professional and technical status. It is dedicated to the study of all problems that may arise in the exercise of the archivist's profession, and the results of these studies have often had a decisive influence on the orientation of archival policy in France. It is rapidly expanding, just as the archivai profession itself.

L'historien de demain et la constitution des fonds d'archives - Voisin, Jean-Claude (Gazette des archives, 1979)

Les généalogistes et les Archives - Wolff, Christian (Gazette des archives, 1979)
Genealogists and archives. Difficultes encountered and examples of solutions adopted by several archive institutions to meet the increasing number of genealogists. The growing importance of this category of researchers and the risks which they inflict on the preservation of documents make it advisable that archivists adopt a common attitude in their relations with genealogists. Better organisation and discipline of genealogists themselves would make these relations easier.